2022
DOI: 10.3389/frvir.2021.672556
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations for Supporting Mindfulness in Virtual Reality

Abstract: Mindfulness practice involves bringing one’s attention to the present moment and noticing events as they unfold with a non-judgmental attitude of acceptance. Although mindfulness has been shown to reduce stress and improve mental health, it can be challenging to learn mindfulness techniques. Recent years have seen an interest in using virtual reality (VR) to help people learn mindfulness by immersing users in virtual settings that support an external focus of attention and reduce everyday environmental distrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Further exploration has revealed that current VR technology can be effectively applied to short-term gaze tasks, while long-term gaze tasks remain to be explored [33]. Research has suggested that the combination of VR and exercise for short periods may yield some psychological improvements compared with VR or exercise alone, and may increase some cognitive and emotional benefits, such as enhanced enjoyment, energy, reduced fatigue, and concentration [34]. This result also suggests that the combination of physical activity and VR will be markedly conducive to improved attention.…”
Section: Comparative Analysis Of the Differences Between Preand Post-...mentioning
confidence: 99%
“…Further exploration has revealed that current VR technology can be effectively applied to short-term gaze tasks, while long-term gaze tasks remain to be explored [33]. Research has suggested that the combination of VR and exercise for short periods may yield some psychological improvements compared with VR or exercise alone, and may increase some cognitive and emotional benefits, such as enhanced enjoyment, energy, reduced fatigue, and concentration [34]. This result also suggests that the combination of physical activity and VR will be markedly conducive to improved attention.…”
Section: Comparative Analysis Of the Differences Between Preand Post-...mentioning
confidence: 99%
“…Figure 2 shows the screenshot of an application. However, it is better to reduce the interaction and distraction in the virtual environment (VE) [10]. Most meditation methods require the user to close their eyes for better results.…”
Section: Virtual Reality For Meditationmentioning
confidence: 99%
“…Regular mindfulness practice is beneficial for mental health, but mindfulness can be challenging to implement, with environmental and personal distractors frequently identified as obstacles. Virtual reality may address these issues by offering an immersive environment for practicing mindfulness and by assisting the user to orient attention to the present moment within a customized virtual setting (Seabrook, 2020;Kelly et al, 2022;Drigas, Mitsea & Skianis, 2022). Various relaxation techniques could benefit from merging with virtual reality (VR) technologies, as these technologies are easily applicable, involving, and user-friendly (Mazgelytė et al, 2021).…”
Section: Virtual Reality In Mindfulnessmentioning
confidence: 99%